Distant ionospheric photoelectron energy peak observations at Venus. (August 2015) - Coates, A.J.; Wellbrock, A.; Frahm, R.A.; Winningham, J.D.; Fedorov, A.; Barabash, S.; Lundin, R.
Abstract: The dayside of the Venus ionosphere at the top of the planet׳s thick atmosphere is sustained by photoionization. The consequent photoelectrons may be identified by specific peaks in the energy spectrum at 20–30 eV which are mainly due to atomic oxygen photoionization. The ASPERA-4 electron spectrometer has an energy resolution designed to identify the photoelectron production features. Photoelectrons are seen not only in their production region, the sunlit ionosphere, but also at more distant locations on the nightside of the Venus environment. Here, we present a summary of the work to date on observations of photoelectrons at Venus, and their comparison with similar processes at Titan and Mars. We expand further by presenting new examples of the distant photoelectrons measured at Venus in the dark tail and further away from Venus than seen before. The photoelectron and simultaneous ion data are then used to determine the ion escape rate from Venus for one of these intervals. We compare the observed escape rates with other rates measured at Venus, and at other planets, moons and comets. We find that the escape rates are grouped by object type when plotted against body radius. Highlights: Observation of ionospheric protoelectrons with sunlight absent, implying transport. Observation of ionospheric photoelectron peaks at 2.3 Venus radii along tail. Measurement of Venus escape rate from photoelectron measurements. Comparison of Venus escape rate with other solar system objects.